Base Editing in Plants: Applications, Challenges, and Future Prospects - Azameti, Mawuli K.; Dauda, Wadzani Palnam (Frontiers in Plant Science, 2021)
The ability to create targeted modifications in the genomes of plants using genome editing technologies has revolutionized research in crop improvement in the current dispensation of molecular biology. This technology has attracted global attention and has been employed in functional analysis studies in crop plants. Since important agronomic traits are confirmed to be determined by single nucleotide polymorphisms; improved crop varieties could be developed by programmed and precise conversion of targeted single bases in the genomes of plants. One novel genome editing approach which serves this purpose is base editing. Base editing directly makes targeted and irreversible base conversion without creating double-strand breaks (DSB).This technology has recently gained quick acceptance and adaptation because of its precision, simplicity, and multiplex capabilities. This review focuses on the generation of different base-editing technologies and how efficient they are in editing nucleic acids. Emphasis is placed on the exploration and applications of these base editing technologies to enhance crop production. The review also highlights the drawbacks and the prospects of this new technology.